2015
DOI: 10.1136/bmjopen-2015-009088
|View full text |Cite
|
Sign up to set email alerts
|

Can clinical features be used to differentiate type 1 from type 2 diabetes? A systematic review of the literature

Abstract: ObjectiveClinicians predominantly use clinical features to differentiate type 1 from type 2 diabetes yet there are no evidence-based clinical criteria to aid classification of patients. Misclassification of diabetes is widespread (7–15% of cases), resulting in patients receiving inappropriate treatment. We sought to identify which clinical criteria could be used to discriminate type 1 and type 2 diabetes.DesignSystematic review of all diagnostic accuracy studies published since 1979 using clinical criteria to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 26 publications
3
100
0
3
Order By: Relevance
“…We attempted to ensure the majority with Type 1 diabetes were not included in the sensitivity analysis by excluding those with an age at diagnosis of diabetes of ≤ 30 years . However, we acknowledge that this exclusion may misclassify some.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted to ensure the majority with Type 1 diabetes were not included in the sensitivity analysis by excluding those with an age at diagnosis of diabetes of ≤ 30 years . However, we acknowledge that this exclusion may misclassify some.…”
Section: Discussionmentioning
confidence: 99%
“…Because of differences in characteristics within the South Asian population, a subgroup analysis was also performed. Finally, sensitivity analysis was performed excluding individuals with probable Type 1 diabetes by removing those diagnosed with diabetes aged ≤ 30 years .…”
Section: Methodsmentioning
confidence: 99%
“…acanthosis nigricans) are more common in children and adolescents with type 2 diabetes than type 1 diabetes. In adults, a systematic review of clinical indicators identified age at diagnosis of diabetes <30 to 40 years, and time to needing insulin <1 to 2 years as more predictive of type 1 diabetes than body mass index (BMI) (4).…”
Section: Tablementioning
confidence: 99%
“…Thus, there is advocacy to perform bariatric surgery in patients with type 2 diabetes at body mass index (BMI) as low as 30 kg/m 2 [2], and prospective studies have begun to evaluate patients with even lower BMI [3]. Performing bariatric surgery in patients at a lower BMI increases the likelihood that surgical candidates may include patients with type 1 diabetes who have been misdiagnosed as having type 2 diabetes [4]. …”
Section: Introductionmentioning
confidence: 99%